Dynamic characteristics of a curved steel–concrete composite cable-stayed bridge and effects of different design choices. (December 2021) - Briseghella, Bruno; Fa, Guanzhe; Aloisio, Angelo; Pasca, Dag; He, Leqia; Fenu, Luigi; Gentile, Carmelo
Abstract: The paper presents and discusses the dynamic response of a curved cable-stayed bridge in Venice (Italy). Two distinct experimental campaigns in 2010 and 2011 led to identifying the bridge dynamic characteristics in operational conditions. The dynamic identification included the characterization of both the deck and cables response. The authors developed a highly refined finite element (FE) model of the bridge, mirroring up to twelve experimental modes. An updating procedure drove the estimate of the optimum parameters associated with the lowest discrepancy with the experimental modal parameters. The calibrated model was the base of a parametric analysis on the effects of the deck curvature, cables arrangement and tower cross-section inertia on the bridge dynamics. Specifically, the authors developed fourteen FE models of the bridge distinguished by the lack and different arrangement of the stay cables, the increasing value of the deck curvature and the tower cross-section inertia. The analysis intends to quantify the impact of the design choices of cable-stayed bridges on the modal parameters.